1994
DOI: 10.1002/jor.1100120315
|View full text |Cite
|
Sign up to set email alerts
|

Technique for in vivo measurement of the three‐dimensional kinematics and laxity characteristics of the ankle joint complex

Abstract: We introduce here a technique to measure the three-dimensional kinematics and laxity characteristics of the ankle joint complex in vivo. The system consists of an optoelectric, kinematic data acquisition system that is used to measure the motion of the ankle joint complex in response to controlled moments applied through a system of pneumatic actuators. As a first step toward development of the method into a quantitative diagnostic tool for injuries of ankle ligaments, we addressed the following questions: (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 27 publications
2
16
0
1
Order By: Relevance
“…Serious skin breakdown in the spinal cord injury population has been reported most frequently over the ischial tuberosities [24] due to concentrated high pressure over bony prominences, which has been considered the most important etiologic factor in pressure ulcer formation in wheelchair users [7]. These facts favorably correspond to the results predicted from our FE analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Serious skin breakdown in the spinal cord injury population has been reported most frequently over the ischial tuberosities [24] due to concentrated high pressure over bony prominences, which has been considered the most important etiologic factor in pressure ulcer formation in wheelchair users [7]. These facts favorably correspond to the results predicted from our FE analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, knowing if ankle-complex motion between ankles in the same individual differs is imperative for accurate diagnosis. To date, few investigators have quantified differences in the uninjured ankle complex for right and left or dominant and nondominant motion, 4,20,21 primarily because a reliable and repeatable method for quantifying anklecomplex motion has been unavailable. [22][23][24] Our data are far more comprehensive than the data that normally are used to evaluate ankle-complex motion, except when researchers use a device similar to the Hollis Ankle Arthrometer as an evaluation tool.…”
Section: Limb Dominancementioning
confidence: 99%
“…18,25,26 These findings of symmetry were consistent with previous reports of the mechanical laxity characteristics of the ankle complex between legs. 4,20,21 Based on data obtained using 3-dimensional kinematics, Stefanyshyn and Engsberg 20 determined that ranges of motion for inversion, eversion, and total I-E were not different between the right and left legs in participants with no history of ankle injury. Siegler et al 21 noted no differences for inversion, eversion, or total I-E rotation comparisons of left and right ankles.…”
Section: Limb Dominancementioning
confidence: 99%
“…2,3,13,14 With inversion loading, no authors of biomechanical studies have reported end-range stiffness characteristics for the intact ankle or for the ankle with combined lesions of the ATFL and CFL despite reporting increased instability. [14][15][16][17][18][19] Therefore, the mechanical property of stiffness may be important to understanding how injury affects joint stability. Given the lack of information on the behavior of the viscoelastic properties of the ankle complex after ankle ligament injury, our understanding of the characteristics of the passive connective tissues before and after injury could be enhanced by examining these effects.…”
mentioning
confidence: 99%